Quantitative discrimination between oil and water in drilled bore cores via Fast-Neutron Resonance Transmission Radiography. (December 2016) - Vartsky, D.; Goldberg, M.B.; Dangendorf, V.; Israelashvili, I.; Mor, I.; Bar, D.; Tittelmeier, K.; Weierganz, M.; Bromberger, B.; Breskin, A.
Abstract: A novel method utilizing the Fast Neutron Resonance Transmission Radiography is proposed for non-destructive, quantitative determination of the weight percentages of oil and water in cores taken from subterranean or underwater geological formations. The ability of the method to distinguish water from oil stems from the unambiguously-specific energy dependence of the neutron cross-sections for the principal elemental constituents. Monte-Carlo simulations and initial results of experimental investigations indicate that the technique may provide a rapid, accurate and non-destructive method for quantitative evaluation of core fluids in thick intact cores, including those of tight shales for which the use of conventional core analytical approaches appears to be questionable. Highlights: We describe a method of Fast-Neutron Resonance Transmission (FNRT) radiography for a non-destructive, specific and quantitative determination of oil and water content in core samples and provide preliminary results of simulations and accelerator studies of laboratory samples. The method measures the average liquid/dry-core-weight ratio in the path traversed by the fast neutrons regardless of the object shape, thickness or distribution. In principle the entire length of an intact core, within its protective sleeve can be scanned along the core length, providing information about the content distribution. The fluid weight fractions in the sample are determined independently, thus the ratio of oil-to-rock weight-ratio is independent of the water content. This is not the case in conventional thermal neutron radiography, where the assigned water and oil contents are unavoidably correlated due to their sensitivity to hydrogen content only. FNRT radiography method is suitable also for non-destructive fluid content determination in tight shales for which the traditional core analysis methods appear to be inadequate due to their very small porosity and permeability.